Effects of loading positions on the activation of trunk and hip muscles during flywheel and dumbbell single-leg Romanian deadlift exercises - Mo, Ryan Chun Yin; Ngai, Derrick Chung Wang; Ng, Chapman Cheuk Man; Sin, Kenson Ho Sang; Luk, Jim Tze Chung; Ho, Indy Man Kit (Frontiers in Physiology, 2023)
The study compared the surface electromyographic (sEMG) activities of trunk and hip muscles during single-leg Romanian deadlift (SLRDL) exercises using a flywheel and dumbbell with different loading positions (ipsilateral and contralateral). Method: Twelve active male subjects with at least two years of strength training experience (age: 26.73.3 years; weight: 73.96.2 kg) participated in this study. sEMG in the percentage of maximum voluntary isometric contraction of four SLRDL exercises (ipsilateral and contralateral loading position for dumbbell and flywheel) in a randomized order for superior gluteus maximus (SGM), inferior gluteus maximus (IGM), gluteus medius (GM), biceps femoris (BF), erector spinae (ES), external oblique (EO), and adductor longus (AL) were measured. One-way repeated measure ANOVA with Bonferroni adjustment (statistical significance at 0.05) and the non-clinical magnitude-based decision with a standardized difference were performed for statistical analysis. Results: The overall results demonstrated a very high level of SGM (105.4 to 168.6%) and BF (69.6 to 122.4%) muscle activities. A significant moderate increase of sEMG signals in GM, IGM, and ES (dominant side) and a large increase in SGM activity during concentric action when the loading position of flywheel SLRDL was changed from ipsilateral to the contralateral side. No significant difference was observed between flywheel and dumbbell SLRDL exercises. Conclusion: Strength coaches may adopt dumbbell or flywheel SLRDL exercises using the contralateral loading position to simultaneously strengthen the hip extensors and trunk stabilizers effectively.